A systematic review of the effectiveness of technological interventions for caregivers of people with dementia: effects on quality of life and psychoemotional variables - Ferrero-Sereno, Patricia; Mendoza-Muñoz, María; Palomo-López, Patricia; Carlos-Vivas, Jorge; Luna-Castaño, Patricia; Caballero-De la Calle, Raquel; Ángel García-Garrido, Miguel; Muñoz-Bermejo, Laura (Frontiers in Public Health, 2025)
BackgroundInformal caregivers of people with dementia present high levels of burden, emotional distress and low social support. Technology-based home-based interventions are presented as an alternative to providing health education, emotional support and caregiver training.ObjectiveTo evaluate the effectiveness of technological interventions on health-related quality of life (HRQoL) and the management of psychoemotional aspects in family caregivers of people with dementia.MethodsA systematic literature review (SLR) was conducted using the Web of Science, PubMed and Scopus electronic databases, including all studies up to 7 February 2025.ResultsIn the review, 7,230 studies were initially identified, but only 13 met the eligibility criteria. The interventions reviewed differed in methodology when examining their impact on target variables. However, on-demand, internet- or telephone-based interventions with training activities and contact with professionals seem to improve quality of life and psychoemotional variables such as anxiety, depression and overload.ConclusionTechnological interventions using the internet and mobile applications may be useful for informal caregivers of people with dementia as they can improve quality of life and psychoemotional aspects. The interventions reviewed differed in terms of instruments and protocols when examining their impact on caregiver well-being. Therefore, more research is needed to further investigate these methodologies in order to optimize their impact and adapt them to the diverse realities of caregivers of people with dementia.